Evolution and hotspots in breast cancer organoid research: insights from a bibliometric and visual knowledge mapping study (2005-2024) - Wu, Tao; Li, BaiXin; Lei, Hao; Zhao, FuXing; Liu, Zhen (Frontiers in Oncology, 2025)
BackgroundBreast cancer is the most common malignancy among women globally. Organoid technology has emerged as a pivotal tool in breast cancer research due to its advantages in modeling tumor heterogeneity and the microenvironment. Despite rapid advancements in this field, a systematic bibliometric analysis to delineate research trends and challenges is lacking. This study aimed to analyze the research landscape, hotspots, and future directions in the field of breast cancer organoids from 2005 to 2024.MethodsPublications related to breast cancer organoids published between January 2005 and March 2024 were retrieved from the Web of Science Core Collection. Bibliometric tools (CiteSpace and VOSviewer) were employed to analyze collaboration networks (countries/institutions), author contributions, keyword co-occurrence clusters, and burst keywords.ResultsOver the past two decades, the annual publication output on breast cancer organoids has shown continuous growth. The 1618 included English publications garnered a total of 7,323 citations, with a mean citation count of 35.20 per article. The United States (n=666) and China (n=257) contributed over 50% of the publications. Harvard University was the most productive institution. Mina J. Bissell authored the highest number of publications (n=17). High-frequency keywords centered on personalized therapy, immunotherapy, and 3D bioprinting. Burst keyword analysis identified “gene expression” and “signaling pathways” as emerging trends (2019–2024). Key research hotspots include the application of patient-derived organoids (PDOs) for drug screening, co-culture modeling of the tumor microenvironment (TME) with immune components, and the integration of 3D bioprinting technologies.ConclusionThis study represents the first comprehensive bibliometric analysis to elucidate the evolution and research hotspots in breast cancer organoid research in recent years. The findings provide a thorough summary of the major achievements, persistent challenges, and future frontiers within this rapidly advancing field.